2011
DOI: 10.1128/mcb.05447-11
|View full text |Cite
|
Sign up to set email alerts
|

High-Mobility Group A2 Protein Modulates hTERT Transcription To Promote Tumorigenesis

Abstract: The high-mobility group A2 gene (HMGA2) is one of the most frequently amplified genes in human cancers. However, functions of HMGA2 in tumorigenesis are not fully understood due to limited knowledge of its targets in tumor cells. Our study reveals a novel link between HMGA2 and the regulation of human telomerase reverse transcriptase (hTERT), the catalytic subunit of telomerase, which offers critical insight into how HMGA2 contributes to tumorigenesis. The expression of HMGA2 modulates the expression of hTERT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 64 publications
(88 reference statements)
0
38
0
Order By: Relevance
“…Human let-7 miRNA (LentimiRa-GFP-hsa-let-7 Vector, mh10004) and HMGA2 short hairpin RNA (shRNA) in piLenti-siRNA-GFP (I009810b) were purchased from Applied Biological Materials Inc.. Lentiviral production in human embryonic kidney (HEK) 293T cells was as we previously described (21). For stable infection, 8 Â 10 4 cells were plated in each well of 6-well plates.…”
Section: Immunohistochemistry and Western Blotmentioning
confidence: 99%
See 1 more Smart Citation
“…Human let-7 miRNA (LentimiRa-GFP-hsa-let-7 Vector, mh10004) and HMGA2 short hairpin RNA (shRNA) in piLenti-siRNA-GFP (I009810b) were purchased from Applied Biological Materials Inc.. Lentiviral production in human embryonic kidney (HEK) 293T cells was as we previously described (21). For stable infection, 8 Â 10 4 cells were plated in each well of 6-well plates.…”
Section: Immunohistochemistry and Western Blotmentioning
confidence: 99%
“…As an important regulator of cell growth, differentiation, apoptosis, and transformation, HMGA2 interacts with many different transcription factors such as E2F1 to influence the expression of numerous genes (20). Recently, we also found that HMGA2 may promote tumorigenesis through modulation of human telomerase reverse transcriptase (hTERT) transcriptional activity (21). Multiple studies have identified a negative correlation between reduced expression of the let-7 miRNA family and overexpression of Ras/HMGA2 in various human cancer tissues (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…S5 A and B). Previous work showed that Hmga2 overexpression displaces histone deacetylase (HDAC) from chromatin and causes increased acetylation of histone H3 on target gene promoters (22,35). We performed immunoblotting and immunofluorescence assays to characterize the epigenetic changes induced by Hmga2 overexpression and found a notable increase in histone acetylation at H3 lysine 9/14 in Hmga2-UGSM cells (Fig.…”
Section: Sustained Overexpression Of Hmga2 In Stromal Cells Is Requirmentioning
confidence: 85%
“…This is intriguing given the propensity of these cells for escape from telomere-driven crisis and cellular transformation via telomerase reactivation (Jones et al 2014). Conjointly, we sequence-verified fusion junctions within the HMGA2 (Li et al 2011) gene (Chr12q14.3) and Chr3p21.31 region implicated in the regulation of telomerase activity ( Fig. 3C; Cuthbert et al 1999) from LIG3 −/− and PARP1 −/− samples.…”
Section: A-and C-nhej Of Dysfunctional Human Telomeresmentioning
confidence: 85%